Intraspecific variation in growth response to drought stress across geographic locations and genetic groups in Coffea canephora. Issue 1 (3rd January 2023) - Kiwuka, Catherine; Vos, Jan; Douma, Jacob C.; Musoli, Pascal; Mulumba, John W.; Poncet, Valérie; Anten, Niels P. R.
Abstract: Uganda lies within the drier end of the natural distribution range of Coffea canephora and contains unexplored genetic material that could be drought‐adapted and useful for developing climate‐resilient varieties. Using water treatment: (i) ample and (ii) restricted‐water, the response of 148 genotypes were studied comprising wild, feral and cultivated C. canephora . Biomass allocation, standing leaf area and leaf area growth data were collected. Linear mixed effect models and PCA were used to the analyze effect of water treatment on genotypes from different: (i) cultivation status, (ii) genetic groups and (iii) locations. We also assessed the relationship between drought tolerance for relative growth rate in leaf area (RGRA), total number of leaves (TNL), total leaf area (TLA) and total leaf dry weight (TLDW) of genotypes at final harvest. Restricted‐water reduced RGRA across genetic groups (3.2–32.5%) and locations (7.1–36.7%) but not cultivation status. For TNL, TLA and TLDW, genotypes that performed well in ample‐water performed worse under restricted‐water, indicating growth‐tolerance trade‐off. Drought tolerance in RGRA and TNL were negatively correlated with wetness index suggesting some degree of adaptation to local climate. Findings indicate a growth‐tolerance trade‐off within this tropical tree species and drought tolerance of Uganda's C. canephora is somewhat associated with local climate. Abstract : Drought tolerance within C. canephora is negatively linked to growth. Drought tolerance of Uganda's C. canephora is weakly though significantly linked to the local climate. Intraspecific diversity, associated with adaptation to local conditions, can be exploited in breeding for climate‐resilient cultivars.